PENGARUH SUBTITUSI TEPUNG SORGUM PUTIH DALAM PEMBUATAN VANILLA CUPCAKE TERHADAP KUALITAS FISIK DAN DAYA TERIMA KONSUMEN - Fairuz, Nadhira Alya; S, I Gusti Ayu Ngurah; Dahlia, Mutiara (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This research seeks to analyze the impacts of substituting white sorghum flour in the making of vanilla cupcakes on both their physical quality and consumer acceptance. This research was carried out at the Pastry and Bakery Laboratory of Culinary Education, Faculty of Engineering, State University of Jakarta in July 2022 - January 2024. The method used in this research is the experimental method involving vanilla cupcakes with white sorghum flour substitution of 20 percent, 30 percent, and 40 percent. A consumer acceptability test was conducted on 30 semi-trained panelists evaluating various organoleptic aspects. The statistical analysis, utilizing Analysis of Variance (ANOVA) for the physical quality test, revealed a significant influence of white sorghum flour substitutions (20%, 30%, and 40%) on both cupcakes rising power and stability. After conducting the Friedman Test on several aspects, results showed that there is no statistically significant difference between treatments on these following aspects: 1) the color of crumbs; 2) sorghum aroma; 3) sweetness; and 4) the texture of the top of the cupcake. On the other hand, the test showed that there is a statistically significant difference between treatments on the following aspects: 1) butter aroma; 2) the taste of sorghum; 3) crumbs texture; and 4) the color of the top of the cupcake. Further investigation using Tukey’s test is necessary for the aspects with observed differences. Ultimately, the most preferred product was the vanilla cupcakes with a 20 percent sorghum flour substitution. Keywords: consumer acceptability, physical quality, vanilla cupcake, white sorghum flour